Quantitative Early Warning of Floor Water Inrush Based on Deep Learning: Joint Response of Microseismic Three-Dimensional Kernel Density and Hydrodynamics - Hang Li; Xianjie Hao; Jinyi Ji; Huaixiang Yang; Wantong Lin; Sheng Zhang; Xinlei Cui (Rock Mechanics and Rock Engineering, 2026)

Pyrolysis of lime dried sewage sludge in a fixed-bed reactor: Effects of the addition amount of lime - Dan Lin; Wantong Kai; Xing Xie; Yusuf Makarfi Isa; Alexander Kozlov; Maxim Penzik; Shihong Zhang; Bin Li (Fuel, 2026)

Self-healing, highly stretchable, recyclable PU-curcumin elastomer with substrate-sensitive solid-state fluorescence - Linjie Wei; Xiubin Xu; Hongchun Mu; Wantong Lin; Jiahui Tang; Jieran Li; Jianwei Liu; Haitao Dong; Danfeng Yu; Xu Wu (Chemical Engineering Journal, 2025)

Catalytic pyrolysis of paper mill sludge over self-sourced CaO/biochar catalyst under different temperatures - Wantong Kai; Xing Xie; Dan Lin; Yusuf Makarfi Isa; Alexander Kozlov; Maxim Penzik; Bin Li (Fuel, 2025)

Blue light-emitting diode promotes mineralization of stem cells from the apical papilla via cryptochrome 1/Wnt/β-catenin signaling - Lin Ye; Hao Li; Wantong Zhang; Yan Zhou; Xiaorong Lan; Yao Wang (Journal of Molecular Histology, 2025)

Steam gasification of lime dried sewage sludge: Effects of temperature and addition of lime - Dan Lin; Wantong Kai; Xing Xie; Alexander Kozlov; Maxim Penzik; Bin Li (Fuel, 2024)

Different microbial functional traits drive bulk and rhizosphere soil phosphorus mobilization in an alpine meadow after nitrogen input - Bing Han; Yicheng He; Ji Chen; Yufei Wang; Lina Shi; Zhenrong Lin; Lu Yu; Xiaoting Wei; Wantong Zhang; Yiyi Geng; Xinqing Shao; Shangang Jia (Science of The Total Environment, 2024)

Natural forests promote phosphorus retention in soil - Zhen Yu; Zhou Guoyi; Lei Liu; Stefano Manzoni; Philippe Ciais; Daniel Goll; Josep Peñuelas; Jordi Sardans; Wantong Wang; Jie Zhu; Lin Li; Junhua Yan; et al. (Global Change Biology, 2022)
Soil phosphorus (P) availability often limits plant productivity. Classical theories suggest that total P content declines at the temporal scale of pedogenesis, and ecosystems develop toward the efficient use of scarce P during succession. However, the trajectory of ecosystem P within shorter time scales of succession remains unclear. We analyzed changes to P pools at the early (I), middle (II), and late (III) stages of growth of plantation forests (PFs) and the successional stages of natural forests (NFs) at 1969 sites in China. We found significantly lower P contents at later growth stages compared to earlier ones in the PF ( p p

An engineering site suitability index (ESSI) for the evaluation of geological situations based on a multi-factor interaction matrix - Kun Li; Yanjun Shang; Wantong He; Daming Lin; Muhammad Hasan; Kaiyang Wang (Bulletin of Engineering Geology and the Environment, 2019)

Modification of rock mass strength assessment methods and their application in geotechnical engineering - Daming Lin; Kaiyang Wang; Kun Li; Wantong He; Weixing Bao; Renmao Yuan; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2017)

Deformation and failure of a tunnel in the restraining bend of a strike–slip fault zone: an example from Hengshan Mountain, Shanxi Province, China - Daming Lin; Renmao Yuan; Yanjun Shang; Weixing Bao; Kaiyang Wang; Zhongjian Zhang; Kun Li; Wantong He (Bulletin of Engineering Geology and the Environment, 2017)

Modifications to the GSI for granite in drilling - Daming Lin; Yan Sun; Wei Zhang; Renmao Yuan; Wantong He; Bo Wang; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2014)